ANALISIS PEMBERDAYAAN MASYARAKAT USAHA MIKRO KECIL DAN MENENGAH (UMKM) KECAMATAN RENGAT OLEH DINAS KOPERASI DAN UMKM KABUPATEN INDRAGIRI HULU - Romauli Romauli; Lilis Suriani (UIR Press, 2018)
Micro, small and medium enterprises (SMEs) is a business activity that is able to expand employment and provide economic services to the wider community and can play a role in the process of equalization and improvement, public revenues, boost economic growth, and play a role in realizing national stability. The purpose of this study was to determine and explain how the process of empowerment of micro, small and medium enterprises (SMEs) Rengat by the District Department of Cooperatives and SMEs Indragiri Hulu, and identify any obstacles that occur in the community development micro, small and medium Rengat subdistrict. In this study, using the theory of empowerment by Gina Kartasasmita (Adam) which states that empowerment can be seen from three sides, namely, Pemungkinan is to create an atmosphere or climate that allows the community potential to develop optimally, should be able to rid the society of the boundaries of cultural and structural impeding strengthening is to strengthen the knowledge and ability of the community to solve problems and meet their needs independently, as well as the protection is to protect the public is weak from being oppressed by the powerful and the weak, thereby eliminating all forms of discrimination and domination. The population in this study include the Head of Department of Cooperatives and SMEs, Head of SME, Head of Controlling and Business Development, as well as the Society who follow guidance by the Department of Cooperatives and SMEs Indragiri Hulu. And the entire population were sampled using census techniques. The collection of data from respondents was conducted by distributing questionnaires, and subsequent researchers also melaklukan interview, documentation and observation to determine the outcome of community development micro, small and medium enterprises (SMEs) the District Rengat. After data collection is done, then analyzed by using percentages to determine how many respondents who expressed a good, fairly good, or not good, based on the analysis of the obtained results of the research conducted and concluded that community development micro, small and medium enterprises (SMEs) Rengat by the District Department of Cooperatives and SMEs Indragiri Hulu in the category